'Do you have a future when you are 93?' Frail older person's perceptions about the future and end of life - a qualitative interview study in primary care - Anna Olaison; Elisabet Cedersund; Jan Marcusson; Magnus Nord; Annette Sverker (Taylor & Francis Group, 2022)
AbstractObjective To explore frail older persons' perceptions of the future and the end of life.Design Qualitative content analysis of individual semi-structured interviews.Setting Nine primary health care centres in both small and middle-sized municipalities in Sweden that participated in the intervention project Proactive healthcare for frail elderly persons.Subjects/Patients The study includes 20 older persons (eight women and 12 men, aged 76-93 years).Main outcome measures Frail older persons' perceptions of the future and end of life.Results The analysis uncovered two main categories: Dealing with the future and Approaching the end of life. Dealing with the future includes two subcategories: Plans and reflections and Distrust and delay. Approaching the end of life includes three subcategories: Practical issues, Worries and realism, and Keeping it away.Conclusion This study highlights the diverse ways older people perceive future and the end of life. The results make it possible to further understand the complex phenomenon of frail older persons' perceptions on the future and the end of life.KEY POINTSThe study found that older persons described their future as contradictory- with a broad spectrum of approaches, where some wanted to deal with these subjects and others wanted to ignore them.•Older persons that consciously planned for the future had tactics that often were related to goals that functioned as motivators to live longer.•Those who adopted a more passive approach did not think about what the future might hold in terms of losing autonomy and deteriorating health.•Older persons that approached end of life in a more proactive way wanted to plan practical arrangements around death but often found it hard to address this issue with relatives.•Those older persons that had a more passive approach to end of life preferred not to think about those issues, and some explicitly stated that they did not want to address the final period of life.